The dual-function of HSP70 in immune response and tumor immunity: from molecular regulation to therapeutic innovations - Zhang, Beining; Qi, Ruiqun (Frontiers in Immunology, 2025)
Heat shock protein 70 (HSP70) is a highly conserved molecular chaperone that plays a core role in assisting protein folding and maintaining cellular homeostasis. In recent years, studies have revealed that HSP70 has dual functions in immune regulation: on the one hand, it enhances immune responses by activating non-specific immunity (such as Toll-like receptor 2/4 (TLR2/4) signaling pathways) and specific immunity (such as cross-presentation of antigens, T helper 1 (Th1)/T helper 17 (Th17) differentiation); on the other hand, it inhibits excessive immune reactions by inducing the differentiation of regulatory T cells (Treg) and promoting the secretion of anti-inflammatory factors [such as interleukin-10 (IL-10)]. In cancer, the duality of HSP70 is also very prominent: it can drive tumor progression through pathways such as inhibiting apoptosis, promoting angiogenesis, and tumor metastasis, and it can also inhibit tumor growth by activating immunogenic cell death (ICD), enhancing antigen presentation, and natural killer (NK) cell activity. This review aims to systematically analyze the immune regulatory functions of HSP70, focusing on its dual regulatory mechanisms and the “double-edged sword” nature of HSP70 in tumor immunotherapy and the innovative nature of targeted strategies, as well as providing a theoretical basis and research directions for precision medicine in the treatment strategies of related diseases.